2000
DOI: 10.1007/s004250000356
|View full text |Cite
|
Sign up to set email alerts
|

Phototolerance of lichens, mosses and higher plants in an alpine environment: analysis of photoreactions

Abstract: Adaptation to excessive light is one of the requirements of survival in an alpine environment particularly for poikilohydric organisms which in contrast to the leaves of higher plants tolerate full dehydration. Changes in modulated chlorophyll fluorescence and 820-nm absorption were investigated in the lichens Xanthoria elegans (Link) Th. Fr. and Rhizocarpon geographicum (L.) DC, in the moss Grimmia alpestris Limpr. and the higher plants Geum montanum L., Gentiana lutea L. and Pisum sativum L., all collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
46
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 39 publications
6
46
0
Order By: Relevance
“…PSII fluorescence quenching in response to desiccation has been reported previously for chlorolichens (Sigfridsson and Öquist, 1980;Lange et al, 2001) and desiccation-tolerant bryophytes (Heber et al, 2000). Our data confirm that this phenomenon applies to desiccation-tolerant cyanolichens, chlorolichens, and green algae, which is consistent with the report by Lange et al (1989).…”
Section: Discussionsupporting
confidence: 93%
“…PSII fluorescence quenching in response to desiccation has been reported previously for chlorolichens (Sigfridsson and Öquist, 1980;Lange et al, 2001) and desiccation-tolerant bryophytes (Heber et al, 2000). Our data confirm that this phenomenon applies to desiccation-tolerant cyanolichens, chlorolichens, and green algae, which is consistent with the report by Lange et al (1989).…”
Section: Discussionsupporting
confidence: 93%
“…Last studies (e.g. Heber et al 2000Heber et al , 2006Heber et al , 2007, however, indicated that there is another effective quencher in photosynthetic apparatus of PS II of desiccating lichens. It is not related to zeaxanthin formation and independent on light.…”
Section: Discussionmentioning
confidence: 99%
“…Upon exposure to water, an immediate increase in fluorescence, back to F O , is observed, followed by a resumption of normal PSII activity as indicated by a return of F V upon exposure to saturating light flashes (Heber et al, 2000;Green et al, 2002). This ability to resume photosynthesis almost immediately after hydration of desiccated lichens is an adaptation to their particular cycles of wetting and dehydration.…”
mentioning
confidence: 99%